Pengaruh Manajerial Kepala Sekolah dalam Meningkatan Kompetensi Guru PAI pada Pendidikan Dasar - Agung Muharom; Ade Hermansyah; Kun Nurachadijat (Institut Madani Nusantara, 2021)
Quality education requires human resources, a characteristic of quality education is the collaboration of supervisors, school principals, and teachers who must be able to better manage educational institutions because it will have an impact on teacher competence. Education is the most important element in improving human resources as a whole, because education management must be oriented towards better change. This study aims to determine the managerial influence of school principals in increasing student competence in the field of Islamic religious education. The research used a descriptive qualitative approach, because the symptoms, implications of information and information from the observations during the research process were naural. The results of the study resulted in the First Managerial Planning for school principals in improving student competence in MIN 5 Sukabumi Regency and at SDN CBM Baros Sukabumi City in accordance with predetermined planning procedures or implementing existing aspects. Second, the managerial implementation of school principals in improving student competence in MIN 5 Sukabumi Regency and at SDN CBM Baros Sukabumi City by examining teacher performance documents in detail, and providing guidance and guidance to teachers in improving peadagogical competence. Third, the evaluation of the managerial implementation of school principals in improving student competence in MIN 5 Sukabumi Regency and at SDN CBM Baros Sukabumi City is always carried out to measure the level of success in the implementation of supervision activities.